Gut Microbiome-Derived Metabolite Trimethylamine N-Oxide Induces Aortic Stiffening and Increases Systolic Blood Pressure With Aging in Mice and Humans. Issue 2 (10th May 2021) - Brunt, Vienna E.; Casso, Abigail G.; Gioscia-Ryan, Rachel A.; Sapinsley, Zachary J.; Ziemba, Brian P.; Clayton, Zachary S.; Bazzoni, Amy E.; VanDongen, Nicholas S.; Richey, James J.; Hutton, David A.; Zigler, Melanie C.; Neilson, Andrew P.; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Aging is associated with stiffening of the large elastic arteries and consequent increases in systolic blood pressure (SBP), which together increase cardiovascular disease risk; however, the upstream mechanisms are incompletely understood. Using complementary translational approaches in mice and humans, we investigated the role of the gut microbiome-derived metabolite trimethylamine N-oxide (TMAO) in age-related aortic stiffening and increased SBP. Aortic stiffness was measured using carotid-femoral or aortic pulse wave velocity (PWV) in humans and mice, respectively. Study 1: Plasma TMAO concentrations were elevated ( P <0.001) in healthy middle-aged to older (6.3±5.8 µmol/L) versus young (1.8±1.4 µmol/L) humans and positively related to carotid-femoral PWV ( r 2 =0.15, P <0.0001) and SBP ( r 2 =0.09, P <0.001), independent of traditional cardiovascular risk factors. Study 2: Dietary supplementation with TMAO increased aPWV in young mice and exacerbated the already elevated aPWV of old mice, accompanied by increases in SBP of ≈10 mm Hg in both groups. TMAO-supplemented versus control-fed mice also had higher intrinsic mechanical stiffness of the aorta (stress-strain testing) associated with higher aortic abundance of advanced glycation end-products, which form crosslinks between structural proteins to promote aortic stiffening. Study 3: Ex vivo incubation of aortic rings with TMAO increased intrinsic stiffness, which was attenuated by the advanced glycation end-products crosslink breaker alagebrium and prevented by inhibition of superoxide signaling. TMAO induces aortic stiffening and increases SBP via formation of advanced glycation end-products and superoxide-stimulated oxidative stress, which together increase intrinsic wall stiffness. Increases in circulating TMAO with aging represent a novel therapeutic target for reducing risk of aortic stiffening-related clinical disorders.